Pelatihan Pembuatan Alat Peraga Ilmu Pengetahuan Bumi Antariksa bagi Kelompok Guru SMP dan SMA Lab. Undiksha Singaraja - Pujani, Ni Made (International Journal of Community Service Learning, 2018)
This service on Science and Technology for Community (IbM) was done for the teachers who teach Geography and Outer Space  (IPBA) at SMP and SMA Lab Undiksha Singaraja. The activity was done in the form  of  training and tutoring in making  teaching aids for IPBA, the training and tuturing in materials development used inquiry approach, and the tutoring was implemented in IPBA teaching using materials that had been developed. This activity was aimed at  improving  knowledge and skill in practicum for the group of teachers of IPBA at SMP and SMA Lab. Undiksha Singaraja to solve the constraints in the teaching of IPBA. The core implementation in the form of in service and on service was started on 16th June, 2017 until 30th October, 2017. The evaluation of the activity jwas done to the process and the output of the activity. The results of the evaluation showed that the IbM activity for the teachers of IPBA at SMP and SMA Lab. Undiksha ran well according to the plan. The teachers at the partner school were enthusiastic and engaged in the activity. Almost all of them were able to improve their skill in developing teaching materials for IPBA using inquiry approach, they could make teaching aids according to Student’s Worksheets developed, and were able to implement  the materials and teaching aids produced in teaching in the classroom.